PERANAN DWANGSOM DALAM PENYELESAIAN SENGKETA PELANGGARAN MEREK DI PENGADILAN NIAGA - , Chandra Gita Dewi; , Drs. Paripurna S.H., M.Hum. LL. M ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research about the role of dwangsom (forced money) in dispute settlement of trademark infringement was aimed to obtain an answer about how dwangsom can be applied in trademark infringement law suit, why brand owners are not interested in suing about dwangsom, and how the role of dwangsom and the benefit of dwangsom in those brand dispute settlements. This research was conducted by using literature and field research. Field research was held in Commercial Court at Central Jakarta District Court and Teguh Samudera and partners Law Office. The methods which were used in this study are documents review and field researchs with doing an interview with Commercial judges and former Chief of Jakarta Pusat civil court in 2007-2010, also advocate in Jakarta area, which is in Teguh Samudera advocate Law Office and Jakarta law Office. The result indicate that dwangsom which is ruled in Rv can be applied in dispute settlement of trademark infringement particularly for termination penalty all acts which are related in brand usage. Dwangsom plays role to accelerate the execution of court decision since it can suppress the condemned to run the court decision voluntarily. The existence of dwangsom in narrow scope of treademark infringement has led to the opportunities used as a punishment becomes smaller.